1984
DOI: 10.1177/00220345840630081701
|View full text |Cite
|
Sign up to set email alerts
|

Materials Science Bond Strength Between Dentin and Restorative Resins Mediated by Mixtures of HEMA and Glutaraldehyde

Abstract: We investigated the bond strength between restorative resin and dentin pre-treated with mixtures of HEMA and glutaraldehyde. It is suggested that the mixture acts by forming a chemical bond of HEMA molecules to a collagen-glutaraldehyde reaction complex. Subsequently applied resin will then co-polymerize with the collagen-linked methacrylate groups. Statistical analysis of the results from varying mixtures of HEMA and glutaraldehyde revealed that the bond strength was highly dependent on the HEMA concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
3
5

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(101 citation statements)
references
References 9 publications
4
89
3
5
Order By: Relevance
“…Dentin priming was primarily developed by Munksgaard and Asmussen, even though they did not fully understand the underlying mechanism 1) . They explained that dentin priming improved the efficacy of dentin adhesives because of the chemical activation of dentin collagen by glutaraldehyde.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentin priming was primarily developed by Munksgaard and Asmussen, even though they did not fully understand the underlying mechanism 1) . They explained that dentin priming improved the efficacy of dentin adhesives because of the chemical activation of dentin collagen by glutaraldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…Dentin primer was first developed and introduced by Munksgaard and Asmussen, whereby it was reported that the tensile bond strength of resin monomers to flat dentin surface was significantly improved when the latter was pretreated with an aqueous mixture of 2-hydroxyethyl methacrylate (2-HEMA) and glutaraldehyde after conditioning with ethylenediaminetetraacetic acid 1) . They explained that the priming mechanism was mediated by the amino group in dentin collagen -which was activated by glutaraldehyde and polymerized with 2-HEMA 2) .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it is clinically significant to improve the bond strength to dentin for the one-step bonding system. In particular, it is important that resin monomer polymerize and harden on the demineralized and moistened dentin surface in order to enhance the bond strength to dentin [33][34][35][36][37] . As a measure to improve the degree of conversion with resin monomer, the addition of polymerization accelerator is considered.…”
Section: Discussionmentioning
confidence: 99%
“…In 1984, Munksgaard and Asmussen reported that pretreatment of EDTA-treated dentin with an aqueous mixture of 2-hydoxyethyl methacrylate (2-HEMA) and glutaraldehyde significantly increased the shear bond strength of the resin monomer composed of Bis-GMA and tri-ethylene glycol di-methacrylate 6) . Such a pretreatment between dentin conditioning and application of dentin bonding agent was clinically introduced as dentin priming.…”
Section: Introductionmentioning
confidence: 99%